Atherosclerotic Lesions in Hypertensive Subjects - A Human Autosy Study (Medical Forum Monthly, 2024)
Objective: To assess the incidence and severity of atherosclerotic lesions in hypertensive subjects in our population. Study design: Prospective descriptive observational study. Place and duration of study: Mortuary of Forensic Department, King Edward Medical University Lahore and Pathology Department of Allama Iqbal Medical College Lahore. This study was completed in one and a half year. Subjects and Methods: A total of 130 human autopsies were carried out in the mortuary of King Edward Medical University Lahore. Heart, aorta and its major branches were collected. History was taken from the close relative of deceased for hypertension. One to four areas of tissue were taken for each artery and aorta for histological examination. The section were stained with Haemotoxylin and Eosin stain. Different special stains were also performed on all cases to differentiate different components of atherosclerotic lesions. Results: The fibrolipid plaques, complicated lesions and calcified lesions were present in a predominant number of cases in aorta and its major branches, except the fibrolipid plaques were less dominant in the right coronary artery, the complicated lesions were seen less frequently in the right coronary artery and the left renal artery and the calcified lesions were observed less dominantly in the thoracic aorta, anterior descending branch and circumflex branch of left coronary, innominate artery, coelic artery, superior mesenteric artery, inferior mesenteric artery and renal arteries. The calcified lesions were absent in the right coronary artery. Conclusion: This study although preliminary but basic and observational in nature indicates the considerable severity of raised atherosclerotic lesions in hypertensive subjects in our population